Botulinum toxin type A with or without needle electromyographic guidance in patients with cervical dystonia - Wu, Chuanjie (Springerplus, 2016)
AIM: To investigate the efficacy and safety of electromyography (EMG)- and palpation-guided botulinum toxin type A injection in cervical dystonia (CD) patients. METHODS: In this randomized, controlled trial, 68 CD patients were randomly allocated to two groups, receiving botulinum toxin type A injections guided by either palpation (Group A) or EMG (Group B). The primary endpoint is defined as the difference in the Tsui score between groups at 16 weeks. The secondary endpoints were the visual analog scale (VAS) and Hospital Anxiety and Depression Scale (HADS) scores and Clinical and Patient Global Impression of Change (CGIC and PGIC). RESULTS: Sixty-five patients completed the study. No significant difference was observed in the Tsui score between groups A and B at 4, 8, and 12 weeks after treatment (p > 0.05). However, 16 weeks after treatment, the Tsui score of group A was significantly higher than that of group B. For both groups, the degree of pain at each time point during follow-up significantly reduced after treatment. However, no significant difference was observed in VAS scores between the two groups. Interestingly, the patient HADS score decreased without statistical significance 8 weeks following treatment. No significant difference in HADS scores was observed between the two groups. Additionally, there was no significant difference in PGIC and CGIC between the two groups. However, CGIC was significantly higher than PGIC. No significant difference in adverse reactions was observed between groups. CD patients treated with EMG guidance experienced a significantly more pain at the injection site but a significantly lower adverse event occurrence rate of dysphagia when compared to CD patients treated with palpation guidance only. CONCLUSIONS: CD patients treated with EMG guidance experienced a prolonged benefit as measured by the Tsui scale when compared to CD patients treated with palpation guidance alone. EMG-guided injection resulted in a lower incidence of dysphagia and higher incidence of discomfort at the injection site than palpation-guided injection.